Rancang Bangun Sistem Monitoring Cash Flow Menggunakan Metode Waterfall untuk Mempermudah Pelaporan di Sekolah Tinggi Teknologi Terpadu Nurul Fikri - Amalia Amalia; Roro Mawar Amalia; Bambang Harie Wiyono; Adhari Cahya Mahendra; Betty Amalia (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
In line with the rapid advancement of digital technology, the need for an efficient, integrated, and technology-based financial management system has become  critical, particularly for educational institutions such as STT-NF. The manual management of financial reports, especially cash flow statements used spreadsheets continues to pose significant challenges, including the risk of data entry errors, delayed reporting, and the lack of real-time visibility into the institution's financial condition. This study aims to develop a web application for cash flow monitoring system using the waterfall methodology to address these issues. The waterfall model was selected due to its systematic and structured approach. The system was developed using ReactJS for the frontend, NodeJS for the backend, and PostgreSQL as the database management system. To verify system functionality, testing was conducted using the black box testing method. The results of the testing indicate that all developed features of the cash flow monitoring system functioned according to the specified requirements and operated optimally. Therefore, the system is expected to provide tangible benefits in supporting the performance of the Finance Department at STT-NF as well as the foundation, by enhancing real-time financial visibility and delivering accurate information to facilitate faster & more informed decision-making.